Effect of inoculum levels and interaction of Macrophomina phaseolina and Fusarium solani on root rot severity of jojoba seedlings - SATISH LODHA, M.D. BOHRA and (Indian Phytopathology, 2002)
Field experiments were conducted at the Central Arid Zone Research Institute, Jodhpur, Rajasthan, India, to determine the effect of 3 inoculum densities of M. phaseolina and F. solani singly or in combination on root infection in jojoba (Simmondsiachinensis). Seedling germination was not adversely affected in the soil infested with inoculum levels and combinations of M. phaseolina and F. solani. However, reduction in plant growth was the primary effect of the pathogens on jojoba seedlings. Both pathogens individually reduced plant height. In general, reduction in plant height was greater in F. solani infected seedlings compared with those infected with M. phaseolina. There was a negative correlation between increasing inoculum levels of M. phaseolina and F. solani and the dry root and shoot weights of jojoba seedlings. The synergistic effect was pronounced in the interaction treatment, where 30-36% and 7-39% reduction in root and shoot weights, respectively, was recorded when compared with the individual infections of these pathogens.